2021
DOI: 10.1007/s00018-021-03927-2
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation regulates the expression of the negative transcriptional regulators ID2 and ID4 during OPC differentiation

Abstract: The differentiation of oligodendrocyte precursor cells (OPCs) into myelinating oligodendrocytes is the prerequisite for remyelination in demyelinated disorders such as multiple sclerosis (MS). Epigenetic mechanisms, such as DNA methylation, have been suggested to control the intricate network of transcription factors involved in OPC differentiation. Yet, the exact mechanism remains undisclosed. Here, we are the first to identify the DNA-binding protein inhibitors, Id2 and Id4, as targets of DNA methylation dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 53 publications
1
27
0
Order By: Relevance
“…The involvement of DNA methylation in oligodendrocyte differentiation has been investigated previously by us and other researchers (6,13,14,32). Using rodent-derived OPCs or mouse models for MS, it has been shown that the presence of DNA methylation enzymes, such as DNMT1 and DNMT3a, is crucial for oligodendrocyte differentiation during development and remyelination (14,15).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The involvement of DNA methylation in oligodendrocyte differentiation has been investigated previously by us and other researchers (6,13,14,32). Using rodent-derived OPCs or mouse models for MS, it has been shown that the presence of DNA methylation enzymes, such as DNMT1 and DNMT3a, is crucial for oligodendrocyte differentiation during development and remyelination (14,15).…”
Section: Discussionmentioning
confidence: 96%
“…DNA methylation, for instance, is a stable yet at the same time dynamic epigenetic mark that translates environmental stimuli to alterations in gene expression and subsequent cellular behaviour. We and others have previously shown that DNA methylation contributes to physiological OPC differentiation (13, 14). In addition, DNA methylation is also required for remyelination, as shown in a mouse model for focal demyelination (15).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Intrinsic factors include age-related decline of histone deacetylation and methylation in OPCs and oligodendrocytes (by reduced HDAC class I expression), enhancing the heterochronic expression of transcriptional inhibitors [e.g., inhibitor of DNA-binding (Id)4] as well as global hypomethylation by downregulation of Dnmt1 in OPCs of aged mice (245)(246)(247). Likewise, DNA methylation of ID2/ID4 allows OPC differentiation, but their methylation levels were lower in MS lesions on human brain samples than in controls (248). Extrinsic factors from the OPC environment can also affect their differentiation.…”
Section: Oligodendrocytesmentioning
confidence: 99%